Mechanical properties and accuracy of removable partial denture frameworks fabricated by digital and conventional techniques: A systematic review - Souza Curinga, Míria Rafaelli; Claudino Ribeiro, Anne Kaline; de Moraes, Sandra Lúcia Dantas; do Egito Vasconcelos, Belmiro Cavalcanti; da Fonte Porto Carreiro, Adriana; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2023)
Statement of problem: Providing a removable partial denture (RPD) can be a complex, time-consuming, and error-prone procedure. Computer-aided design and computer-aided manufacturing (CAD-CAM) techniques have shown promising clinical outcomes; however, the influence of manufacturing techniques on the properties of RPD components is unclear. Purpose: The purpose of this systematic review was to determine the accuracy and mechanical properties of RPD components fabricated with conventional and digital methods. Material and methods: This study followed the guidelines of the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) and was registered on the international prospective register of systematic reviews (PROSPERO) database (CRD42022353993). An electronic search was conducted on PubMed/MEDLINE, Scopus, Web of Science, and the Cochrane Library in August 2022. Only in vitro studies comparing the digital with the lost-wax casting technique were included. The quality of the studies was assessed by using the methodological index for nonrandomized studies (MINORS) scale. Results: Of the 17 selected studies, 5 evaluated the accuracy of RPD components as well as the mechanical properties, 5 studies evaluated only the component accuracy, and another 7 evaluated only the mechanical properties. The accuracy was similar regardless of the technique, with discrepancies within clinically acceptable values (50 to 426.3 μm). The surface roughness was higher for 3D-printed clasps and lower for milled clasps (P<.05). The metal alloy significantly influenced the porosity, with the highest number of pores obtained by casting for Ti clasps and by rapid prototyping for Co-Cr clasps. Conclusions: In vitro studies showed that the digital technique provided similar accuracy to that of the conventional technique within a clinically acceptable range. The manufacturing technique influenced the mechanical properties of RPD components.